Proceedings of the 6th International Conference on Digital Health Conference 2016
DOI: 10.1145/2896338.2896360
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Indicators of Mood

Abstract: Positive wellbeing in the workplace is tied to better health. However, lack of wellbeing in the workplace is a serious problem in the U.S, is rising continually, and can lead to poor health conditions. In this study we investigate factors that might be associated with workplace wellbeing. We report on an in situ study in the workplace of 40 information workers whose mood was tracked for 12 days. We used a mixed-methods study using Fitbit actigraphs to measure sleep and physical activity, computer logging, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Here we see a directionality switch with some of the objective features. Sleep duration was modeled with a positive regression coefficient with pre-post change PHQ-9 (eg, higher sleep duration modeled a worse PHQ-9 change score) almost throughout the study period, but during the last quarter, it changed to a negative regression coefficient, which is consistent with the literature, as depicted in Figure 2 [48,51]. These findings highlight the importance of transparency regarding the analysis methods.…”
Section: Discussionsupporting
confidence: 84%
“…Here we see a directionality switch with some of the objective features. Sleep duration was modeled with a positive regression coefficient with pre-post change PHQ-9 (eg, higher sleep duration modeled a worse PHQ-9 change score) almost throughout the study period, but during the last quarter, it changed to a negative regression coefficient, which is consistent with the literature, as depicted in Figure 2 [48,51]. These findings highlight the importance of transparency regarding the analysis methods.…”
Section: Discussionsupporting
confidence: 84%
“…Several recent studies have used wearable devices to estimate sleep quality and sleep-related parameters [15][16][17][18] and analyzed the relationship between sleep and depression [19][20][21]. Miwa et al [19] estimated sleep quality by detecting rollover movements during sleep and observed a significant difference in sleep quality between nondepressed and depressed people.…”
Section: Introductionmentioning
confidence: 99%
“…Miwa et al [19] estimated sleep quality by detecting rollover movements during sleep and observed a significant difference in sleep quality between nondepressed and depressed people. Mark et al [20] estimated the sleep duration of 40 information workers for 12 days using a Fitbit wristband and found that sleep duration was positively correlated with mood. DeMasi et al [21] found that sleep was significantly related to changes in depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Although we will provide a focused review of relevant works that have used audio data to predict or measure mood and anxiety disorders, there is a wealth of research that has looked at using many different data sources to investigate, predict, or measure the severity of many characteristics of health and mental health disorders. Interested readers are directed to work that has investigated subjects' general mood and mental health [9][10][11][12][13][14][15], substance abuse [16,17], depression [18][19][20][21][22][23][24], bipolar disorder [25][26][27][28][29], anxiety disorders [30][31][32], and schizophrenia [33,34]. The most commonly used sources of passively collected smartphone data in these works include subjects' geolocation (ie, GPS data), screen activity and phone usage time, SMS and phone metadata, and physical activity and motion sensor data.…”
Section: Previous Workmentioning
confidence: 99%